Comparative pharmacokinetics of intramuscular artesunate and artemether in patients with severe falciparum malaria. - Hien, T; Davis, T; Chuong, L; Ilett, K; Sinh, D; Phu, N; Agus, C; Chiswell, G; White, N; Farrar, J (2004)
The first-dose pharmacokinetic properties of intramuscular (i.m.) artesunate (ARTS; 2.4 mg/kg immediately [stat], followed by 1.2 mg/kg i.m. daily) and artemether (ARM; 3.2 mg/kg i.m. stat, followed by 1.6 mg/kg i.m. daily) were compared in Vietnamese adults with severe falciparum malaria. A total of 19 patients were studied; 9 received ARTS, and 10 received ARM. ARTS was absorbed very rapidly; concentrations in plasma peaked between 1,362 and 8,388 nmol/liter (median, 5,710 nmol/liter) within 20 min of injection and then declined with a median (range) half-life (t(1/2)) of 30 (3 to 67) min. ARTS was hydrolyzed rapidly and completely to the biologically active metabolite dihydroartemisinin (DHA). Peak DHA concentrations in plasma ranged between 1,718 and 7,080 nmol/liter (median, 3,060 nmol/liter) and declined with a t(1/2) of 52 (26 to 69) min. In contrast, ARM was slowly and erratically absorbed. The absorption profile appeared biphasic. Maximum ARM concentrations in plasma ranged between 67 nmol/liter (a value close to the 50% inhibitory concentration for some Plasmodium falciparum isolates) and 1,631 nmol/liter (median, 574 nmol/liter) and occurred at a median (range) of 10 (1.5 to 24) h. There was relatively little conversion to DHA. After i.m. injection in cases of severe malaria, absorption of the water-soluble ARTS is rapid and extensive, whereas the oil-based ARM is slowly and erratically absorbed, with relatively little conversion to the more active DHA. On the basis of this pharmacological study, parenteral ARTS is preferable to ARM as an initial antimalarial therapy, particularly in the most seriously ill patients. These findings should be formally assessed by a randomized clinical trial.